Finding And Proving Seafloor Massive Sulphide Resources - Julian Malnic (International Marine Minerals Society, 2001)
Various natural, commercial, engineering and operational factors govern the evolution of approaches taken in the exploration for Seafloor Massive Sulphides (SMS) and in delineating the resource. These stages are prerequisites to the proposed mining of SMS deposits. This paper presents and analyses these factors from the view of an SMS exploration company that is pioneering the exploration of this rich alternative source of zinc, copper and gold. Current exploration practices developed by Marine Scientific Research (MSR) workers for SMS deposits are expected to give way to industry-generated methods as the SMS exploration industry gathers momentum. The exploration process falls into three phases that are described below: Prospecting (locating targets), Indicating Resources, and Measuring Mineral Resources Considerable streamlining of the SMS exploration process will accelerate the rate of discovery. The economics of SMS mining are projected to be superior to comparable terrestrial mining operations in both operating cash cost and capital terms.